Albania : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for a Waiver of Nonobservance of Performance Criterion, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2004)
This paper focuses on Albania's Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), Request for a Waiver of Nonobservance of Performance Criterion, and Financing Assurances Review. Performance since the third review has been satisfactory overall, although 2003 fiscal revenue fell short of the ambitious budget targets. All quantitative performance criteria for end-March 2004 were met. The end-December 2003 indicative target for net credit to government was also met substantially despite revenue and external assistance.